Characterization of Ebola Virus Disease (EVD) in Rhesus Monkeys for Development of EVD Therapeutics - Travis Warren (Viruses, 2020)
Recent Ebola virus (EBOV) outbreaks in West Africa and the Democratic Republic of the Congo have highlighted the urgent need for approval of medical countermeasures for treatment and prevention of EBOV disease (EVD). Until recently, when successes were achieved in characterizing the efficacy of multiple experimental EVD therapeutics in humans, the only feasible way to obtain data regarding potential clinical benefits of candidate therapeutics was by conducting well-controlled animal studies. Nonclinical studies are likely to continue to be important tools for screening and development of new candidates with improved pharmacological properties. Here, we describe a natural history study to characterize the time course and order of progression of the disease manifestations of EVD in rhesus monkeys. In 12 rhesus monkeys exposed by the intramuscular route to 1000 plaque-forming units of EBOV, multiple endpoints were monitored for 28 days following exposure. The disease progressed rapidly with mortality events occurring 7−10 days after exposure. Key disease manifestations observed consistently across the infected animals included, but were not limited to, viremia, fever, systemic inflammation, coagulopathy, lymphocytolysis, renal tubular necrosis with mineralization, and hepatocellular degeneration and necrosis.